Histone deacetylase inhibitors mitigate antipsychotic risperidone-induced motor side effects in aged mice and in a mouse model of Alzheimer’s disease - Rodriguez, Guadalupe; Fisher, Daniel W.; McClarty, Bryan; Montalvo-Ortiz, Janitza; Cui, Qiaoling; Chan, C. Savio; Dong, Hongxin (Frontiers in Psychiatry, 2023)
Antipsychotic drugs are still widely prescribed to control various severe neuropsychiatric symptoms in the elderly and dementia patients although they are off-label use in the United States. However, clinical practice shows greater side effects and lower efficacy of antipsychotics for this vulnerable population and the mechanisms surrounding this aged-related sensitivity are not well understood. Our previous studies have shown that aging-induced epigenetic alterations may be involved in the increasing severity of typical antipsychotic haloperidol induced side effects in aged mice. Still, it is unknown if similar epigenetic mechanisms extend to atypical antipsychotics, which are most often prescribed to dementia patients combined with severe neuropsychiatric symptoms. In this study, we report that atypical antipsychotic risperidone also causes increased motor side effect behaviors in aged mice and 5xFAD mice. Histone deacetylase (HDAC) inhibitor Valproic Acid and Entinostat can mitigate the risperidone induced motor side effects. We further showed besides D2R, reduced expression of 5-HT2A, one of the primary atypical antipsychotic targets in the striatum of aged mice that are also mitigated by HDAC inhibitors. Finally, we demonstrate that specific histone acetylation mark H3K27 is hypoacetylated at the 5htr2a and Drd2 promoters in aged mice and can be reversed with HDAC inhibitors. Our work here establishes evidence for a mechanism where aging reduces expression of 5-HT2A and D2R, the key atypical antipsychotic drug targets through epigenetic alteration. HDAC inhibitors can restore 5-HT2A and D2R expression in aged mice and decrease the motor side effects in aged and 5xFAD mice.